PENGARUH SISTEM PENGENDALIAN MANAJEMEN TERHADAP EFEKTIVITAS PENGGUNAAN ANGGARAN PADA DINAS KELAUTAN DAN PERIKANAN KABUPATEN POHUWATO DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERATING - Muhammad Anas (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2016)
The design of an adequate management control system is needed to control the organization to be able to make effective use of the budget is one of the goals of the organization. These goals can be achieved if based on the existence of organizational commitment is also high on all parties involved in the organization. This study aimed to examine the effect of management control systems to the effectiveness of using the budget to the Department of Marine and Fisheries Pohuwato organizational commitment as moderating variable. Based on the results of research and discussion that has been stated previously, the next a number of conclusions, study hypothesis which states management control system in the form of the control structure of management and process management control positive and significant impact on the effectiveness of the use of the budget at the Department of Marine and Fisheries in Pohuwato accepted. The study hypothesis which states the organization's commitment and significant positive effect on the effectiveness of the use of the budget at the Department of Marine and Fisheries in Pohuwato accepted. The study hypothesis which states management control structure and significant positive effect on the effectiveness of the use of the budget at the Department of marine fisheries in Pohuwato organizational commitment as moderating variebel rejected. The study hypothesis which states management control process positive and significant impact on the effectiveness of the use of the budget at the Department of marine fisheries in Pohuwato organizational commitment as moderating variebel accepted. The research hypotheses simultaneously prove that the independent variable that consists of the control structure management (X1), and process management control (X2) and organizational commitment as moderating variable (X3) positive and significant effect on the dependent variable is the effective use of the budget (Y) at the Department marine fisheries in Pohuwato accepted.